Bioformation of boldenone and related precursors/metabolites in equine feces and urine, with relevance to doping control. Issue 2 (21st November 2019) - Viljanto, Marjaana; Kicman, Andrew T.; Walker, Christopher J.; Wolff, Kim; Muir, Tessa; Hincks, Pamela; Biddle, Simon; Scarth, James
Abstract: Boldenone (1‐dehydrotestosterone) is an exogenous anabolic‐androgenic steroid (AAS) but is also known to be endogenous in the entire male horse and potentially formed by microbes in voided urine, the gastrointestinal tract, or feed resulting in its detection in urine samples. In this study, equine fecal and urine samples were incubated in the presence of selected stable isotope labeled AAS precursors to investigate whether microbial activity could result in 1‐dehydrogenation, in particular the formation of boldenone. Fecal matter was initially selected for investigation because of its high microbial activity, which could help to identify potential 1‐dehydrogenated biomarkers that might also be present in low quantities in urine. Fecal incubations displayed Δ1‐dehydrogenase activity, as evidenced by the use of isotope labeled precursors to show the formation of boldenone and boldione from testosterone and androstenedione, as well as the formation of Δ1‐progesterone and boldione from progesterone. Unlabeled forms were also produced in unspiked fecal samples with Δ1‐progesterone being identified for the first time. Subsequent incubation of urine samples with the labeled AAS precursors demonstrated that Δ1‐dehydrogenase activity can also occur in this matrix. In all urine samples where labeled boldenone or boldione were detected, labeled Δ1‐progesterone was also detected. Δ1‐progesterone was not detected any non‐incubated urine samples or following an administration of boldenone undecylenate to one mare/filly. Δ1‐progesterone appears to be a candidate for further investigation as a suitable biomarker to help evaluate whether boldenone present in a urine sample may have arisen due to microbial activity rather than by its exogenous administration. Abstract : Δ1‐steroid biomarkers could potentially be used to distinguish the microbial production of boldenone from its exogenous administration. Δ1‐progesterone was identified as a potential biomarker using fecal matter. Subsequent urine incubation experiments in the presence of selected isotope labeled precursors showed that a labeled form of this biomarker was formed in incubated urine samples where labeled boldenone or boldione were detected, supporting its use as a potential biomarker.